Aspectos bioquímicos da herbivoria de Danaus plexippus (L.) em folhas de Calotropis procera (Ait.) R. Br. - Pereira, Danielle Aragão (2010)
Evidence has been accumulated supporting the role of latex in protecting plants against different aggressors; however it is known that milkweeds are heavily attacked by monarch butterfly, including Calotropis procera. The present study describes the proteolytic activity related to the herbivory of 5th instars of the monarch butterfly, Dannaus plexippus L. (Lepidoptera: Danaidae) fed on diets containing latex proteins, and the proteolytic activity of larvae gut extract on latex proteins. Gut extracts of monarch digested azocasein, BANA and BApNA. The proteolytic activity on azocasein was inhibited by cysteine protease inhibitors such as E-64 and iodoacetamide but it was stronger inhibited by PMSF and leupeptin, serine proteases inhibitors. Gut extracts of monarch digested latex proteins promptly. However, gut extracts did not digest latex proteins from Cryptostegia grandiflora and only barely digested laticifer proteins from Plumeria rubra, two species free of monarch herbivory. Larvae fed on artificial diets containing latex proteins were not affected and growth rate was slightly better compared to control. The protein profile of latex proteins extracted of healthy and attacked plants exhibited visible differences with increasing detection of a protein identified as glycoside hydrolase in latex of attacked plants. The proteolytic, chitinolytc, inhibition protease and anti-oxidative activities not were altered in attacked or injured plants. Results present here give interesting information on resistance of monarch fed on Calotropis procera and suggest that the ability of monarch proteolytic enzymes to promptly digest latex proteins can at least in part explain how the insect overcomes defensive proteins of latex.